Kadozan Chitosan Formulation Enhances Postharvest Quality of Fresh Indian Jujube Fruit - Lian Chen; Yixiong Lin; Hui Li; Qingqing Liu; Yihui Chen (Foods)
Indian jujube fruit is prone to perishing, resulting in a shorter shelf life after harvest. Kadozan is a liquid chitosan formulation that has a significant effect on fruit preservation. In order to explore its efficacy, the quality, and storability indicators of Indian jujube fruit were evaluated during storage at 15 ± 1 °C for 18 days. Results showed that Kadozan-treated fruit exhibited lower respiration rate, relative electrolyte leakage rate, weight loss, and decay index, along with higher firmness and commercially acceptable rate. Furthermore, Kadozan-treated fruit showed higher vitamin C, total sugar, titratable acid, total soluble solids, chlorophyll, and carotenoid contents, L* and h° values, but lower a* and b* values. Principal component analysis and comprehensive score revealed that Kadozan treatment helped preserve the appearance and nutritional qualities of Indian jujube fruit. The best effect was seen with 1:600 Kadozan among three concentrations (1:300, 1:600, 1:900). It was discovered that the commercially acceptable rate of 1:600 Kadozan-treated fruit was 37.5% higher than control fruit while the decay index was 30.5% lower than control fruit at 18 days. Therefore, Kadozan treatment has great substantial implications for the preservation of Indian jujube fruit, providing practical guidance for reducing its postharvest losses.